2015
DOI: 10.1002/lno.10143
|View full text |Cite
|
Sign up to set email alerts
|

The “Melosira years” of Lake Baikal: Winter environmental conditions at ice onset predict under‐ice algal blooms in spring

Abstract: Winter primary production in seasonally ice‐covered lakes historically has not been well studied, but it is increasingly recognized as an important component of lake metabolism. Lake Baikal in Siberia is not only the World's oldest, deepest, and most biologically diverse lake, but also where large under‐ice blooms of the diatom Aulacoseira baicalensis (formerly Melosira) occur in some years. The phenomenon of “Melosira years” is noteworthy both for the intensity of the diatom blooms, in which total under‐ice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 68 publications
6
63
2
Order By: Relevance
“…The lack of NO 3 -N accumulation during early and midwinter in these bog lakes may reflect an absence of nitrification, or coupled nitrification-denitrification. However, NO 3 -N did sometimes accumulate in bog lakes during late winter, suggesting nitrification may be supported by biogenic oxygen during enhanced photosynthesis under thinning ice or clear ice (Katz et al 2015;Kerfoot et al 2008), which has not been commonly demonstrated in bog lakes. In the oligotrophic-mesotrophic lakes, oxic conditions were typically maintained throughout winter.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The lack of NO 3 -N accumulation during early and midwinter in these bog lakes may reflect an absence of nitrification, or coupled nitrification-denitrification. However, NO 3 -N did sometimes accumulate in bog lakes during late winter, suggesting nitrification may be supported by biogenic oxygen during enhanced photosynthesis under thinning ice or clear ice (Katz et al 2015;Kerfoot et al 2008), which has not been commonly demonstrated in bog lakes. In the oligotrophic-mesotrophic lakes, oxic conditions were typically maintained throughout winter.…”
Section: Discussionmentioning
confidence: 87%
“…One consideration is that ecosystem respiration rates derived from fitted nighttime oxygen data reflect integrated oxygen consumption rates, including autotrophic processes such as nitrification, and thus may overestimate aerobic respiration. A second consideration is that photoinhibition of nitrification during the day (French et al 2012) might introduce a diel cycle, especially when clear ice forms (Katz et al 2015), potentially influencing the validity of the assumption that daytime and nighttime ecosystem respiration rates are equal (Winslow et al 2016). These examples reflect upper limits to the amount of biological information that can be extracted from oxygen-based models alone, especially in systems where dissolved oxygen and inorganic carbon are not perfectly coupled, as would be expected when processes such as nitrification contribute substantially to the oxygen dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…What are the ecological circumstances under which speciation occurred, and might these past conditions provide clues to anticipate changes in ecosystem processes in lakes where endemic biota play significant roles? In ancient lakes with a history of extensive speciation at extremes of temperature, or precipitation, anticipating biological changes in response to warming is difficult but potentially important; e.g., Lake Baikal endemics tend to be coldwater stenotherms with optimal growth at low temperatures (e.g., Kozhov ; Kozhova and Izmest'eva ; Bondarenko et al ; Katz et al ; Izmest'eva et al ; Bedulina et al ) and behavioral avoidance of warm water (Timofeyev and Shatilina ; Axenov‐Gribanov et al ; Jakob et al ), while endemic cichlids of the African Rift Lakes are adapted to high temperature but already may be living near physiological maxima. Climate is not the only significant contributor to changes in selective pressures that might affect biodiversity.…”
Section: Future Research Opportunities In Ancient Lakesmentioning
confidence: 99%
“…Katz et al . ; Beall et al . ), whereas other lakes do not appear to have distinct seasonal changes in phytoplankton community composition (Dokulil et al .…”
Section: Introductionmentioning
confidence: 99%